2023
DOI: 10.3390/mi14122252
|View full text |Cite
|
Sign up to set email alerts
|

Development of Microrobot with Optical Magnetic Dual Control for Regulation of Gut Microbiota

Xiaotian Lan,
Yijie Du,
Fei Liu
et al.

Abstract: Microrobots have emerged as a promising precision therapy approach that has been widely used in minimally invasive treatments, targeted drug delivery, and wound cleansing, and they also offer a potential new method for actively modulating gut microbiota. Here, a double-faced microrobot was designed to carry gut bacteria via covalently immobilizing the antibodies, and a corresponding integrated optical and magnetic dual-driving control system was also developed for precise control of the microrobot. The microro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have showcased the precise control of particle orientation through the application of magnetic fields [ 6 , 14 , 15 , 16 , 17 , 18 , 47 ]. In particular, magnetophoresis has been utilized to regulate the movement and direction of particles [ 9 , 43 , 47 , 48 , 49 , 50 ]. Additionally, research conducted in [ 14 , 15 , 16 , 47 ] demonstrated the utilization of a multi-solenoid system to energize magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [16] presents the results of research in medicine, where microrobots controlled by means of optical and magnetic fields were used. Their use was confirmed by experimental and numerical simulation analyses.…”
mentioning
confidence: 99%